Developing goat farm waste management tool to produce organic fertilizer - Hassan Basri, Abdul Mun'im; Abd Rahman, Khairul Aidil Azlin (Universiti Putra Malaysia Press, 2019)
In agriculture, the ‘organic fertilizer’ or popularly known by its trade name, ‘Black Gold’ is the result of livestock faeces that are processed or recycled as manure. This project aimed to develop a specific product for collecting goat manure while cleaning the pen. The clean-and-collect criteria of this product was created to complement the farm worker’s task in working efficiently. The major target of this project was to identify existing cleaning products that can be enhanced for clean-and-collect purpose in the animal pen. Both primary and secondary research data were used in this study. The primary data were collected by interviewing the farm worker and farm officer; both shared information, experiences, and problems during the process of cleaning the goat pen. Data were also collected from observation of the cleaning tools used in the pen. The secondary data were collected from literature review and patents from previous studies including articles, journal, websites, and other documented sources. These data were described and analysed qualitatively in this research. The cleaning process in the pen will become easier with the clean-and-collect product that has been explored in this study. The time spent to clean the pen will be improved as well. In conclusion, the product will clean the pen effectively by collecting goat faeces efficiently. It is therefore feasible to be developed as a waste management tool that can aid in the production of organic fertilizer. Subsequently, this product is also beneficial in terms of income and labour requirements in the farm.